SUBCELLULAR, MOLECULAR AND SUBMOLECULAR MECHANISMS OF ALTERED CONTRACTILITY AND EFFICIENCY OF ENERGY TRANSFORMATION BY MYOCARDIAL MYOFIBRILS IN CHRONIC HEART FAILURE AND MODE OF ACTION OF CARDIAC GLYCOSIDES - N. V. Karsanov; G. V. Sukoyan; T. G. Samsonidze; D. R. Tatulashvili; N. E. Guledani; L. T. Kuchava; V. N. Karsanov (Российский кардиологический журнал, 2000)
The work has been carried out on myocardial bioptates, autopsy and experimental material. In chronic heart failure (CHF) it has been established the sharp decrease of ability of force generation, ATP hydrolysis and economy of energy transduction in myocardial contractile protein (MCPS) at the time of development of energy deficit state and disturbances in Ca-transport system are the key mechanism of CHF development and progression. In contradiction to early and acute HF in CHF myosin-based (as a result of damage of hydrolytic center of myosin head) decrease of intensity of ATP hydrolysis is deposited on the actin-based decrease of value and velocity of generated force and economy of energy transduction in MCPS. The described phenomena in CHF are conditioned on the molecular level by the changes of the structural-conformational state of monomer and protomer of actin and its interaction with myosin heads of thick filament in force generation process. This conclusion has been confirmed in experiments in which are studied the properties of hybrid fibers, reconstructed from failing heart thin filament and normal myosin and vice versa. The actomyosin hypothesis of the mechanism of force generation and energy transduction disturbances in CHF has been suggested. It has been shown that at the submolecular level in actin the distances between Lys61, Tyr69 in subdomain 2 and Cys374 and Cys10 are increased, the conformation mobility of these aminoacidic acids is decreased and microenviroment is changed. These leads to the loosening of outside doman of actin. According to these data together with the data of atomic structure of skeletal muscle actin and 3D reconstruction pattern of cardiac actin from normal and failing heart a hypothetic models for such actins have been reconstructed. The appointed faults have posttranslational character and under the creation of optimal conditions in vitro under the influence of cardiac glycosides (β-acetyldigoxine, β-methyldigoxine and strophantine K) are able to revert, though they are firm.